2003
DOI: 10.2174/0929867033456350
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Water-Soluble Alkylperoxyl Radicals and Superoxide with DNA, Lipoproteins and Phospholipid Vesicles:The Role Played by Electrostatic Forces

Abstract: The role of electrostatic forces in free radical biology is very important but it is all too often overlooked. The radicals discussed in this review include positively-charged, negatively-charged and neutral water-soluble alkylperoxyls and superoxide. Important scientific insights have been gained by generating these radicals in known quantities by the thermal decomposition of simple, "clean", chemical precursors in the presence of potential bio-targets. For example, the abilities of these radicals to damage d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 72 publications
(188 reference statements)
0
8
0
Order By: Relevance
“…Cytoprotection against AAPH. It is known from the work of Ingold and co-workers ( ) that AAPH decomposes with a unimolecular rate constant of 2 × 10 -6 s -1 into two positively charged carbon radicals. These rapidly add oxygen and may, therefore, be represented as + AOO • .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytoprotection against AAPH. It is known from the work of Ingold and co-workers ( ) that AAPH decomposes with a unimolecular rate constant of 2 × 10 -6 s -1 into two positively charged carbon radicals. These rapidly add oxygen and may, therefore, be represented as + AOO • .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, little work has been done on the systematic design of antioxidants targeted toward reducing age-related neurodegenerative disease, but such designer antioxidants are attracting increasing attention now that the principles behind antioxidant design are relatively well understood (6)(7)(8)(9)(10). In a previous work (11) using adherent PC-12 adrenal cells, we subjected the cells to oxidative stress in the form of AAPH (2,2′-azobis (2amidinopropane) hydrochloride), which generates a continuous flux of alkylperoxyl radicals (12)(13)(14)(15). Cytotoxicity studies showed that 1,2-naphthalenediol (1,2-ND) and 1,4-ND were quite toxic and were thus ruled out as potentially useful antioxidants.…”
Section: Introductionmentioning
confidence: 99%
“…The water-soluble 2,2′-azobis(2-amidinopropane) dihydrochloride (known as ABAP28 or AAPH29) has been extensively used to initiate lipid peroxidation,30-32 to explore effects of oxidative stress on cultured cells33-36 and signaling responses associated with inflammation and aging 37. Ingold and co-workers have shown that the thermal decomposition of AAPH in oxygenated neutral solutions generate both strand breaks and base modifications of supercoiled DNA 21-23. In turn, neutral and negatively-charged peroxyl radicals derived from the decomposition of 2-methyl- N -(2-hydroxyethyl)propionamide and 2,2′-azobis[2-methyl- N -(2-hydroxyethyl)propionamide], respectively, were at least two orders of magnitude less effective in generating DNA strand scission.…”
Section: Introductionmentioning
confidence: 99%
“…Persistent inflammation, which is a fundamental physiological defensive reaction against a variety of viral and microbial infections, environmental pollutants, tobacco smoke, and other exogenous factors, becomes harmful if transformed to a chronic form. Oxidative stress associated with chronic inflammation is characterized by the overproduction of reactive oxygen species (ROS) that can cause oxidative damage to diverse biomolecules. These ROS induce peroxidation of membrane lipids and the accumulation of lipid hydroperoxides that break down into reactive intermediates such as electrophilic aldehydes, epoxides, and alkylperoxyl and alkoxyl free radicals. The chemistry and genotoxic effects of covalent DNA adducts generated by electrophilic aldehydes and epoxides derived from lipid peroxidation have been studied extensively. Although oxidative damage to DNA exposed to lipid oxyl radicals has been documented, the detailed mechanisms remain poorly understood due to the complexities associated with the interconversion, fragmentation, and structural characterization of lipid peroxyl and oxyl radicals.…”
Section: Introductionmentioning
confidence: 99%
“…The thermal and photochemical decomposition of azo compounds is a classical approach for the controlled generation of alkylperoxyl radicals . The water-soluble 2,2′-azobis(2-amidinopropane) dihydrochloride [known as ABAP or AAPH ] has been extensively used to initiate lipid peroxidation , to explore the effects of oxidative stress on cultured cells , oxidation of DNA , and signaling responses associated with inflammation and aging . Our own laser flash photolysis experiments have shown that the photolysis of AAPH generates a whole spectrum of free radicals including 2-amidinoprop-2-peroxyl (ROO • ), 2-amidinoprop-2-oxyl (RO • ), and superoxide (O 2 •− ) radicals .…”
Section: Introductionmentioning
confidence: 99%